Equipes globais virtuais: a expeirência de profissionais em banco de investimentos multinacionais - Tsuji, Eduardo Yuji (2009)
Initiated in the 1960’s to the second stage of the Globalization process, led mainly by multinational companies and their strategies for expansion, and supported by advances in information technology and communication resulted in profound changes in organizational structures, from hierarchical models in detriment of more flexible and dynamic models, changing the way of working. This project aimed to study the impact brought by the use of organizational structures based on global networks and global virtual teams to professionals who work at multinational investment banks. The impacts were evaluated through the concept of discontinuities, which is understood as factor or factors contributing to lack of cohesion in situations of collectivity. 15 professionals, from 4 multinational investment banks, were analyzed and individual faceto-face interviews were applied considering the discontinuities and items proposed in the literature (Duarte and Snyder, 1999, Watson-Manheim et al., 2002; Espinosa et al., 2003, Saunders et al., 2004; Jarvenpaa et al., 2004; Zolin et al., 2004, Golden and Veiga, 2005; Chudoba et al., 2005; Dani et al., 2006) for investigation. The results of the analysis of data collected allow inferring that the factors of discontinuities suggested in the study are relevant to practitioners of multinational investment bank. Additionally, we found that although collected and analyzed individually, there is correlation between the discontinuities analyzed, occurring joint or simultaneously in the development of activities of the professionals.